2013
DOI: 10.1111/tra.12125
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Disruption of an EH‐domain Protein Endocytic Complex, Pan1‐End3

Abstract: Pan1 is a multi-domain scaffold that enables dynamic interactions with both structural and regulatory components of the endocytic pathway. Pan1 is composed of Eps15 Homology (EH) domains which interact with adaptor proteins, a central region that is responsible for its oligomerization and C-terminal binding sites for Arp2/3, F-actin, and type-I myosin motors. In this study, we have characterized the binding sites between Pan1 and its constitutive binding partner End3, another EH domain containing endocytic pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
(80 reference statements)
0
12
0
Order By: Relevance
“…The End3 C-terminus was previously shown to bind directly to the middle of Pan1 in vitro ( Tang et al. , 1997 ; Whitworth et al. , 2014 ; Figure 1C ).…”
Section: Resultsmentioning
confidence: 87%
“…The End3 C-terminus was previously shown to bind directly to the middle of Pan1 in vitro ( Tang et al. , 1997 ; Whitworth et al. , 2014 ; Figure 1C ).…”
Section: Resultsmentioning
confidence: 87%
“…End3 is an EF-hand Ca 2+ -binding protein that is required for the internalization of the endocytic vesicle and establishes proper actin patch and cell wall chitin localization [281]. The End3 C-terminus is the site of recruitment and binding by Pan1p to form a stable complex, enabling Pan1p phosphoregulation [282] Sc Pan1 is the only endocytic protein that is essential for viability, and contributes to actin cytoskeletal organization [283].…”
Section: Clathrin-independent Endocytosismentioning
confidence: 99%
“…Sla1 forms a complex with two EH domain-containing late coat proteins, Pan1 and End3 ( Tang et al 1997 ; Tang et al 2000 ). Recently, the specific domains in Pan1 and End3 mediating their interaction were identified, and it was shown that this interaction is required for Pan1 phosphoregulation ( Whitworth et al 2014 ). This Sla1 – Pan1 – End3 trio may be the yeast functional counterpart to mammalian endocytic scaffold/signaling protein Intersectin, which has EH and SH3 domains in a single polypeptide ( Yamabhai et al 1998 ).…”
Section: Cargo Selection and Coat Formationmentioning
confidence: 99%
“…Pan1 and Ent1 also have predicted Glc7 binding sites ( Gardiner et al 2007 ). Recent work shows that Pan1 dephosphorylation and disappearance from patches depends on Pan1 interactions with End3 and recruitment of Scd5 ( Whitworth et al 2014 ). Thus, there is a critical role for the Scd5 – Glc7 complex in regulating the dynamics and behavior of the endocytic machinery at cortical patches ( Chi et al 2012 ).…”
Section: Vesicle Scission and Uncoatingmentioning
confidence: 99%